2017
DOI: 10.1002/jssc.201700014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 4-hydroxyphenyl lactic acid, 4-hydroxyphenyl acetic acid, and 3,4-hydroxyphenyl propionic acid in human urine by ultra-high performance liquid chromatography with fluorescence detection

Abstract: A simple and reliable method was established for simultaneous determination of 4-hydroxyphenyl acetic acid, 4-hydroxyphenyl lactic acid, and 3,4-hydroxyphenyl propionic acid in human urine by high-performance liquid chromatography with fluorescence detection. Solid-phase extraction was used to eliminate the interferences in urine. The separation of three analytes was achieved using a C column and a mobile phase formed by a 95:5 v/v mixture of 50 mmol/L ammonium acetate buffer at pH 6.8 that contained 5 mmol/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Tyrosine levels are known to be altered in liver disease 53 while HPLA has demonstrated carcinogenic activity after long-term subcutaneous injection in mice, 54 and its urinary levels have been observed to be elevated in breast cancer patients. 55 Positive HCC-risk associations were also observed for isatin, L, L-cyclo(leucylprolyl), N1-acetylspermidine and sphingosine-although, very little is known about any physiological roles for these compounds in HCC development. Isatin is a biologically active endogenous metabolite with antioxidant and antiviral effects 56 -properties that may be considered as cancer protective rather than explanatory of our observed positive HCC-risk association.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine levels are known to be altered in liver disease 53 while HPLA has demonstrated carcinogenic activity after long-term subcutaneous injection in mice, 54 and its urinary levels have been observed to be elevated in breast cancer patients. 55 Positive HCC-risk associations were also observed for isatin, L, L-cyclo(leucylprolyl), N1-acetylspermidine and sphingosine-although, very little is known about any physiological roles for these compounds in HCC development. Isatin is a biologically active endogenous metabolite with antioxidant and antiviral effects 56 -properties that may be considered as cancer protective rather than explanatory of our observed positive HCC-risk association.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of urine samples from breast cancer and healthy controls by Zeng et al found that high vanillin, 4-hydroxyphenylacetic acid, 5hydroxyindoleacetic acid and urea were used as biomarkers for breast cancer [22]. Metabolomic analysis of urine samples also showed that high vanillin, 4hydroxyphenylacetic acid, 5-hydroxyindoleacetic acid and urea could be used as biomarkers for breast cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine is an amino acid that originates from the hydroxylation of phenylalanine, 7 precursor of various substances such as catecholamines, presenting a relationship with some types of cancer. [8][9][10] In particular, some studies report variations of pHPAA in hepatocellular carcinoma and breast cancer. [9][10] The guidelines for the diagnosis and follow-up of NETs indicate serum CgA, urinary 5-HIAA, and serum NSE determinations as the gold standard.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] In particular, some studies report variations of pHPAA in hepatocellular carcinoma and breast cancer. [9][10] The guidelines for the diagnosis and follow-up of NETs indicate serum CgA, urinary 5-HIAA, and serum NSE determinations as the gold standard. Previous retrospective preliminary data have reported increased levels of urinary pHPAA in NET patients.…”
Section: Resultsmentioning
confidence: 99%